2015
DOI: 10.1007/s10103-015-1775-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wavelength-dependent hair growth effects on low-level laser therapy: an experimental animal study

Abstract: In this study, we aimed to investigate the wavelength-dependent effects of hair growth on the shaven backs of Sprague-Dawley rats using laser diodes with wavelengths of 632, 670, 785, and 830 nm. Each wavelength was selected by choosing four peak wavelengths from an action spectrum in the range 580 to 860 nm. The laser treatment was performed on alternating days over a 2-week period. The energy density was set to 1.27 J/cm(2) for the first four treatments and 1.91 J/cm(2) for the last four treatments. At the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Since ERK phosphorylation was activated by 830 nm LED light, the increases in growth factors and cytokines seemed to be mediated by the ERK signaling pathway. Kim et al consistently compared the differential effects of PBMT on hair growth using 632, 670, 785, and 830 nm wavelengths and reported that the 830 nm wavelength showed the greatest hair growth promotion in a rat model. In this study, possible growth factors responsible for cell proliferation were IGF‐1, KGF, IL‐6, and IL‐8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ERK phosphorylation was activated by 830 nm LED light, the increases in growth factors and cytokines seemed to be mediated by the ERK signaling pathway. Kim et al consistently compared the differential effects of PBMT on hair growth using 632, 670, 785, and 830 nm wavelengths and reported that the 830 nm wavelength showed the greatest hair growth promotion in a rat model. In this study, possible growth factors responsible for cell proliferation were IGF‐1, KGF, IL‐6, and IL‐8.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of photobiomodulation therapy (PBMT) on hair growth have been demonstrated in clinical and animal studies . Although a recent meta‐analysis revealed that PBMT could be a promising to induce hair growth, it was difficult to assess its clinical efficacy for hair loss disorders .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important parameters to the LLLT is the wavelength, which can determine the depth of penetration and absorption, thus their effects. Since longer wavelengths are absorbed into the deeper layers of biological tissue 31 , and in the present study the aim was to reach the muscle tissue by stimulating the proprioceptive components 2,3,6 , it was chosen infrared 830 nm wavelength. Similar to the wavelength used by Almeida et al 32 , comparing the 830 nm to 660 nm, but found that both wavelengths promoted increased peak power and delayed fatigue of the biceps muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Light has been shown to be directly or indirectly associated with alertness, performance, and mood [30]. It can be used to stimulate hair growth [31] when hair is thinning (max = 830 nm) and to stimulate the production of collagen by the skin. Indeed, all cells contain light-responsive substrates (chromophores like cytochrome c oxidase) whose activity is altered by exposure to select wavebands of light.…”
Section: Introduction To Em Biological Effectsmentioning
confidence: 99%